2008
DOI: 10.1111/j.1574-695x.2008.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Telithromycin inhibits the production of proinflammatory mediators and the activation of NF-κB inin vitro-stimulated murine cells

Abstract: Telithromycin is a ketolide antibiotic with anti-inflammatory properties. To investigate the mechanisms of these effects, we examined the in vitro immunomodulatory activity of telithromycin on murine splenocytes and the murine macrophage cell line RAW 264.7. Spleen cells from BALB/c-untreated mice and RAW 264.7 macrophages were cultured in the presence of telithromycin. Proliferation and apoptosis (colorimetric assay), and cytokine production (enzyme immunoassay) of spleen cells in response to lipopolysacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In chicken spleen cells, active caspase-3 cleaves IB␣, producing a dominant inhibitory form of the protein and ultimately suppressing NF-B activity (4). Additionally, reports have demonstrated that some macrolides, including erythromycin, inhibit NF-B signaling and expression of proinflammatory mediators, such as CXCL8, via mechanisms that have yet to be fully elucidated (2,27,36,56). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chicken spleen cells, active caspase-3 cleaves IB␣, producing a dominant inhibitory form of the protein and ultimately suppressing NF-B activity (4). Additionally, reports have demonstrated that some macrolides, including erythromycin, inhibit NF-B signaling and expression of proinflammatory mediators, such as CXCL8, via mechanisms that have yet to be fully elucidated (2,27,36,56). …”
Section: Discussionmentioning
confidence: 99%
“…This class of antibiotics is known to influence the recruitment and infiltration of neutrophils (23,26,31) and to alter their ability to secrete histotoxic compounds (23) and proinflammatory cytokines (31,50,53). Recent findings also indicate that some macrolides may induce cellular death by apoptosis (3,5,7,8,26) and block NF-B signaling in T lymphocytes, macrophages, or epithelial cells (27,36,56). However, the precise mechanisms underlying the anti-inflammatory and proapoptotic activities of macrolides in neutrophils remain unclear.…”
mentioning
confidence: 99%
“…Proliferation and apoptosis (colourimetric assay) and cytokine production (enzyme immunoassay) of spleen cells in response to LPS and concanavalin A (Con A), and nitric oxide (NO) (colorimetric assay) and cytokine production by lipopolysaccharide-stimulated RAW 264.7 cells were determined [18]. In addition, telithromycin has been found to suppress TNF-alpha production [24].…”
Section: Anti-inflammatory and Immunomodulatory Propertiesmentioning
confidence: 99%
“…Like macrolides, ketolides also inhibit the synthesis of proinflammatory cytokines (TNF, IL-1b, IFNg) and have anti-inflammatory/immunomodulatory properties that may be beneficial to CAP patients [42][43][44][45][46].…”
Section: Introduction and Overviewmentioning
confidence: 99%